2021
DOI: 10.3390/e23010098
|View full text |Cite
|
Sign up to set email alerts
|

High-Entropy Alloys for Advanced Nuclear Applications

Abstract: The expanded compositional freedom afforded by high-entropy alloys (HEAs) represents a unique opportunity for the design of alloys for advanced nuclear applications, in particular for applications where current engineering alloys fall short. This review assesses the work done to date in the field of HEAs for nuclear applications, provides critical insight into the conclusions drawn, and highlights possibilities and challenges for future study. It is found that our understanding of the irradiation responses of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
71
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 176 publications
(85 citation statements)
references
References 176 publications
(395 reference statements)
0
71
1
1
Order By: Relevance
“…Multiple principal element alloys also present unique opportunities to make significant gains with a bcc structure in the form of refractory high/medium-entropy alloys (RHEAs) which are aimed at ultrahigh temperature applications [45][46][47][48] or applications requiring radiation-tolerant materials. 49,50 Early work on RHEAs by Senkov and co-workers, for example, has shown that Nb 25 Mo 25 Ta 25 W 25 and V 20 Nb 20 Mo 20 Ta 20 W 20 alloys can exhibit excellent combinations of strength and ductility (Figure 4a-d), 46 but unfortunately, like most testing on RHEAs, this was performed in compression. At room temperature, both of these HEAs have a yield strength in excess of 1 GPa and ductilities of about 2% failure strains (Figure 4a, c), whereas at elevated testing temperatures up to 1000°C they demonstrated excellent plastic flow properties exceeding ~ 10-15% strains (Figure 4b, d).…”
Section: Strength and Ductility In Bcc Rheasmentioning
confidence: 99%
“…Multiple principal element alloys also present unique opportunities to make significant gains with a bcc structure in the form of refractory high/medium-entropy alloys (RHEAs) which are aimed at ultrahigh temperature applications [45][46][47][48] or applications requiring radiation-tolerant materials. 49,50 Early work on RHEAs by Senkov and co-workers, for example, has shown that Nb 25 Mo 25 Ta 25 W 25 and V 20 Nb 20 Mo 20 Ta 20 W 20 alloys can exhibit excellent combinations of strength and ductility (Figure 4a-d), 46 but unfortunately, like most testing on RHEAs, this was performed in compression. At room temperature, both of these HEAs have a yield strength in excess of 1 GPa and ductilities of about 2% failure strains (Figure 4a, c), whereas at elevated testing temperatures up to 1000°C they demonstrated excellent plastic flow properties exceeding ~ 10-15% strains (Figure 4b, d).…”
Section: Strength and Ductility In Bcc Rheasmentioning
confidence: 99%
“…The multilayer AlCrMoNbZr/(AlCrMoNbZr)N coating with the layer step of 50 nm demonstrated better protective properties compared to 5/5 nm and 10/10 nm multilayers and single-layer AlCrMoNbZr (Figure 6) [117]. Despite the potential application of HEAs as ATF materials for fuel claddings [118][119][120][121], their application as protective coatings is challenging due to possible low temperature eutectics, with Zr alloys and complex oxide scales formed after HT oxidation. [117] with permission by Elsevier.…”
Section: Heas Coatingsmentioning
confidence: 99%
“…Compared to conventional alloys containing only one major element, high entropy alloys (HEAs) [3], an emerging multi-principal element solid solution alloy, exhibit excellent mechanical properties [4,5] and high temperature stability [6,7] due to their complicated random arrangement of alloying elements and the characteristic of local chemical environment at the atomic level. Therefore, HEAs, regarded as a new candidate structural material in nuclear reactors, have become a research hotspot [8,9]. CoCrFeMnNi HEA is one of the earliest studied HEA systems [10], and can form face-centered cubic (FCC) single-phase solid solution structure well.…”
Section: Introductionmentioning
confidence: 99%